Depression, anxiety and stress, during COVID-19 pandemic among midwives in ethiopia: A nationwide cross-sectional survey - Kassahun, Eskeziaw Abebe; Kassie, Belayneh Ayanaw; Tilahun, Sewbesew Yitayih; Bizuneh, Asmamaw Demis (Frontiers in Psychiatry, 2022)
Introduction COVID-19 has rapidly crossed borders, infecting people throughout the whole world, and has led to a wide range of psychological sequelae. Midwives who come close in contact with women while providing care are often left stricken with inadequate protection from contamination with COVID-19. Therefore, this study aimed to assess the level of depression, anxiety, and stress (DASS) among midwives in Ethiopia. Methods A cross-sectional study was conducted from 20 June to 20 August 2020, among 1,691 practicing midwives in Ethiopia. A simple random sampling technique was used to select study participants. Data were collected through a structured telephone interview. A 21-item depression, anxiety, and stress scale (DASS-21) was used. Data were entered using the Google forms platform and were analyzed with SPSS version 24. Both bivariate and multivariable logistic regression analyses were employed. Variables with a p-value < 0.05 in the final model were declared statistically significant. Adjusted odds ratio (AOR) with the corresponding 95% confidence interval (95% CI) was used to determine independent predictors. Results The prevalence of DASS among midwives in Ethiopia was 41.1, 29.6, and 19.0%, respectively. Being female [AOR = 1.35; 95% CI: 1.08, 1.69], working in rural areas [AOR = 1.39; 95% CI: 1.06, 1.82], having poor knowledge of COVID-19 [AOR = 1.40; 95% CI: 1.12, 1.75], having poor preventive practice [AOR = 1.83; 95% CI: 1.47, 2.28], and substance use [AOR = 0.31; 95% CI: 0.17, 0.56] were significantly associated with depression; while, working in the governmental health facility [AOR = 2.44; 95% CI: 1.24, 4.78], having poor preventive practice [AOR = 1,47; 95% CI: 1.16, 1.85], and having poor attitude [AOR = 2.22; 95% CI: 1.04, 1.66] were significantly associated with anxiety. Furthermore, working in rural areas [AOR = 0.57; 95% CI: 0.39, 0.83], substance use [AOR = 2.06; 95% CI: 1.51, 2.81], having poor knowledge [AOR = 1.44; 95% CI: 1.20, 1.90], and having poor preventive practice [AOR = 1.60; 95% CI: 1.23, 2.10] were associated with stress. Conclusion In this study, the overall magnitude of depression, anxiety, and stress were high. Addressing knowledge gaps through information, training, and safety protocols on COVID-19 and the provision of adequate personal protective equipment (PPE) is essential to preserve the mental health of Midwives during COVID-19.